PERTUMBUHAN VEGETATIF JAGUNG PIPILAN (Zea mays L.) PADA TANAH SULFAT MASAM DENGAN PERLAKUAN LINDI TPA SAMPAH DAN ABU SABUT KELAPA - Ruben Tinting Sirenden; Suparno Suparno; Moch Anwar (Agrienvi: Jurnal Ilmu Pertanian, 2023)
This research aims to : 1) Knowing the effect of the interaction between the provision of landfill waste and coconut coir ash on the growth of shelled corn plants. 2) Knowing the best dose of leachate landfill leachate on the growth of shelled corn plants. 3) Determine the best dose of coconut coir ash on the growth of shelled corn plants.This research was conducted from March 2019 to September 2019. Sido Mulyo Village , Bukit Batu District, Palangka Raya City . This study uses a Completely Randomized Design (CRD) compiled factorially with 2 factors. Factor I provision of organic leachate liquid waste landfill + EM4 (50 ml) with 4 levels, namely: B0 = without administration (control), B1 = 14 ml / L per polybag, B2 = 18 ml / L per polybag, B3 = 22 ml / L per polybag. Factor II application of coconut husk ash fertilizer with 3 levels, namely: N0 = without administration (control), N1 = 6 t / ha, N2 = 8 t / ha.The results of the study, the combination of 35 ml / polybag landfill leachate and coconut fiber ash (32.32 g / polybag) (B3N2) had a significant effect on plant height variables with the highest average indigo value of 199.33 cm, the number of leaves with the highest average tilapia is 15.00 strands, the stem diameter with the highest average tilapia is 2.52 mm, the age of male flowering is 49 days, and the dry weight of plants with the highest average tilapia is 466.67 g. The provision of 35 ml / polybag (B3) landfill leachate and coir ash ash to 32.32 g / polybag (N2) gives the highest average yield for all variables observed including plant height, amount leaf, stem diameter, age of male flowering, plant wet weight, and plant dry weight.